Magnetic activation of TREK1 triggers stress signalling and regulates neuronal branching in SH-SY5Y cells - Rotherham, Michael; Moradi, Yasamin; Nahar, Tasmin; Mosses, Dominic; Telling, Neil; El Haj, Alicia J. (Frontiers in Medical Technology, 2022)
TWIK-related K+ 1 (TREK1) is a potassium channel expressed in the nervous system with multiple functions including neurotransmission and is a prime pharmacological target for neurological disorders. TREK1 gating is controlled by a wide range of external stimuli including mechanical forces. Previous work has demonstrated that TREK1 can be mechano-activated using magnetic nanoparticles (MNP) functionalised with antibodies targeted to TREK1 channels. Once the MNP are bound, external dynamic magnetic fields are used to generate forces on the TREK channel. This approach has been shown to drive cell differentiation in cells from multiple tissues. In this work we investigated the effect of MNP-mediated TREK1 mechano-activation on early stress response pathways along with the differentiation and connectivity of neuronal cells using the model neuronal cell line SH-SY5Y. Results showed that TREK1 is well expressed in SH-SY5Y and that TREK1-MNP initiate c-Myc/NF-κB stress response pathways as well as Nitrite production after magnetic stimulation, indicative of the cellular response to mechanical cues. Results also showed that TREK1 mechano-activation had no overall effect on neuronal morphology or expression of the neuronal marker βIII-Tubulin in Retinoic Acid (RA) / Brain-derived Neurotrophic factor (BDNF) differentiated SH-SY5Y but did increase neurite number. These results suggest that TREK1 is involved in cellular stress response signalling in neuronal cells, which leads to increased neurite production, but is not involved in regulating RA/BDNF mediated neuronal differentiation.